Analysis of Tea Competitiveness and Factors Affecting Tea Competitiveness of North Sumatra Province, Indonesia in the Malaysian Market - Nahdudin, Nahdudin; Rahmanta, Rahmanta; Lindawati, Lindawati (Agro Bali : Agricultural Journal, 2025)
Increased exports of North Sumatra tea to the Malaysian market will increase competitiveness. This potential provides added value to the national tea processing industry. The research objectives analyzed the competitiveness of North Sumatra tea in the Malaysian Market and analyzed the factors that affect the competitiveness of North Sumatra tea in the Malaysian Market. The research method uses Revealed Comparative advantage (RCA) and Export Product Dynamic (EPD) to analyze the competitiveness of North Sumatra tea in the Malaysian Market. Multiple Linear Regression to analyze factors that affect the competitiveness of North Sumatra tea in the Malaysian Market. The results showed that North Sumatra has strong comparative but weak competitive competitiveness in the Malaysian Market. The factors that affect the competitiveness of North Sumatra tea are the volume of North Sumatra tea exports, which has a positive and insignificant effect; the domestic price of North Sumatra tea, which has a significant negative effect;. The export price of North Sumatra tea and the export price of Kenyan tea have a negative and insignificant effect on the competitiveness of North Sumatra tea to the Malaysian Market. Please state explicitly specific suggestions for further research.